Author Correction: Tree rings reveal globally coherent signature of cosmogenic radiocarbon events in 774 and 993 CE - Büntgen, Ulf; Wacker, Lukas; Galván, J Diego; Arnold, Stephanie; Arseneault, Dominique; Baillie, Michael; Beer, Jürg; Bernabei, Mauro; Bleicher, Niels; Boswijk, Gretel; Bräuning, Achim; Carrer, Marco; et al. (Nature communications, 2018)
The original version of this Article contained an error in the Data Availability section, which incorrectly read 'All data will be freely available via https://www.ams.ethz.ch/research.html .' The correct version states ' http://www.ams.ethz.ch/research/published-data.html ' in place of ' https://www.ams.ethz.ch/research.html '. This has been corrected in both the PDF and HTML versions of the Article.